The relationship between new product development and organisational performance in Malaysian Electrical & Electronic Industry - Siti Muyassarah, Abd Nasir (2022)
New Product Development (NPD) have received serious attention among manufacturing industries. Electrical and Electronic (E&E) industry contributed higher export value amongst industries and became a dominant sector with the largest contribution to Malaysia’s economic growth. Moreover, Industrial Revolution 4.0 (IR4.0) leads to the application of technology in operations toward manufacturing digitalisation. This is where it spreads the information globally and eliminates the need for a human to do repetitive tasks, as these are then being replaced by automation. Although the linkage between NPD, supplier integration and organisational performance exists in previous literature, the existence of IR4.0 in supplier integration has not been further explored. There were 323 companies selected as a sample from the population of E&E companies in Malaysia. Analyses were done using PLS-SEM. It was found that modular, distinction and flexibility have a direct positive impact on organisational performance. However, the relationship between innovation and organisational performance was not significant. The predictor of modular and flexibility was positively related to IR4.0 in supplier integration. Besides, IR4.0 in supplier integration can predict organisational performance and play an intermediary role in modularity and flexibility. However, the mediation effects of IR4.0 in supplier integration were not significant for distinction and innovation. This study has a significant impact on theoretical contribution as a reference to the industry, academics and students by linking all the independent variables related to NPD, which have never been combined before as additional empirical evidence to the body of knowledge in Malaysia. Secondly, this study benefitted practically for policy makers, manufacturers, managers, engineers, shareholders and directors to focus on modular, distinction, flexibility and IR4.0 in supplier integration to improve organisational performance. Thirdly, the findings established the empirical validity and reliability of the instrument in the E&E industry context.